Peran Infrastruktur Kereta Api Terhadap Perekonomian Daerah - Kuswati, Atik S; Maimunah, Siti; Herawati, Herawati (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Transportation infrastructure has a significant role towards economic development. Railway infrastructure is expected to give a high contribution in regional development. The study was conducted to understand the role of the railway infrastructure in supporting the regional economy by using Gross Regional Domestic Product (GRDP) as a measurement. By using a dynamic spatial econometric models, it is expected to know how big influence the railway infrastructure on GDP and its effect may differ in national and regional levels. The result of model analysis showed that the addition amount of traffic or route service would raise GDP growth by 0.069%, whereas with the addition of traffic or route service frequency will increase GDP grmuth by 0.005%. Modeling results that positively affect GDP grmuth is the amount of traffic or traffic routes and frequency of services or service routes. Both these variables describe the traffic capacity that has a strong correlation with the availability of rail infrastructure. Through the simulation increases the number of paths, then if the total amount of the current trajectory is increased 1.1 times, it can affect GDP growth up to 0.076% while the frequency of traffic can contribute to GDP growth up to 0.005% and the frequency of cross-influence may continue to increase if the number cross frequency was increased.Keywords: railway infrastructure, regional economy